Dynamics of Contraception Use in Indonesia Based on Service Sources at Health Facilities - Ekoriano, Mario; Ardiana, Irma; Rahmadhony, Aditya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
The current use of contraception is dominated by short term methods with a one month drop out rate for contraception pills and injections that contribute 30.6 percent and 46.3 percent, respectively, for women aged 15-49. The high use of short term contraceptives can result in gaps for acceptors to stop using contraception. The analysis aims to investigate switching behaviour among contraceptive users by different source of health facilities both for modern and traditional methods and the analysis also intends to identify sociodemographic factors characterizing switchers. This analysis resulted in four models of sociodemographic factors and their relationship with the possibility of transferring to another contraceptive method which were analyzed using logistic regression in each unit of analysis based on the source of the health facility. Short term contraception is still the favorite, namely injections (50.5 percent) and pills (19.1 percent) are still the main choice for couple of childbearing age. Around 61.2 percent of acceptors who use injectable contraception survive compared to other contraception use in private and community based health facilities. The pattern of family planning use in health facilities in the government sector is at least able to intervene in acceptors in the use of long term contraception which effectively has a lower dropout rate than the dropout rate for short term contraceptives.